Major Mergers Mean Major Offset: Drivers of Intrinsic Scatter in the MGCS–Mh Scaling Relation for Massive Elliptical Galaxies - Veronika Dornan; William E. Harris (The Astrophysical Journal, 2025)
In this work, we determine the total globular cluster (GC) counts and globular cluster system (GCS) total mass estimates for 27 extremely massive elliptical galaxies. The GC 2D spatial distributions of these galaxies were created from photometry of Hubble Space Telescope images using DOLPHOT in the near-IR wavelength range. The projected radial density profiles of these GCSs were determined using a Voronoi-tessellation-based technique introduced in our previous paper. We then plot these galaxies on the GCS–halo mass relation alongside previously studied galaxies in the literature. The relation now extends across seven decades of halo mass. We find that the 1:1 slope of this relation holds out to the highest-mass galaxies, although extremely massive BCG galaxies are shifted to higher GCS masses than their lower-mass galaxy counterparts. We find a negative correlation with massive galaxies’ offset from the GCS–halo mass relation and the steepness of their GCS density profiles, and that this is being driven by the red GC populations. We suggest that the biggest influence in intrinsic scatter in the GCS–halo mass relation for massive galaxies is through a few major mergers resulting in accretion of massive satellites with old, red GC populations, rather than many accretions of small satellites with younger, blue GC populations.